2022
DOI: 10.3390/su141912660
|View full text |Cite
|
Sign up to set email alerts
|

Improvement in Bending Performance of Reinforced Concrete Beams Produced with Waste Lathe Scraps

Abstract: In this study, the impacts of different proportions of tension reinforcement and waste lathe scraps on the failure and bending behavior of reinforced concrete beams (RCBs) are clearly detected considering empirical tests. Firstly, material strength and consistency test and then ½ scaled beam test have been carried out. For this purpose, a total of 12 specimens were produced in the laboratory and then tested to examine the failure mechanism under flexure. Two variables have been selected in creating text matrix… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 26 publications
0
33
0
Order By: Relevance
“…Therefore, cement additives are of interest to reduce cement production [ 4 , 5 ]. Waste is generally defined as residues from industrial production processes, residues arising from the transfer, or product residues that have completed their economic life [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. With the development of modern cities, the decrease in natural resources, climate change, and increasing awareness of environmental protection, there is an urgent need to develop building materials that will reduce greenhouse gas emissions [ 2 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, cement additives are of interest to reduce cement production [ 4 , 5 ]. Waste is generally defined as residues from industrial production processes, residues arising from the transfer, or product residues that have completed their economic life [ 6 , 7 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ]. With the development of modern cities, the decrease in natural resources, climate change, and increasing awareness of environmental protection, there is an urgent need to develop building materials that will reduce greenhouse gas emissions [ 2 , 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Karalar et al [ 34 ] conducted a study that investigated the use of waste lathe scraps in reinforced concrete beams. The results showed that the addition of steel waste lathe scraps increased the compressive strength of the resulting concrete by up to 32.5% when a fibre volume of 3% was used and improved the beam’s mechanical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have been performed using other recycled waste materials such as recycled coal bottom ash, waste lathe scraps, waste lathe fibres, and steel fibres extracted from waste tyres for cement-based composites [ 2 , 8 , 9 , 10 , 11 , 12 , 13 , 14 ] and these studies are also important as they address the reduction of environmental problems. In addition, studies have been published describing the use of waste cellulose-based fibres (i.e., both waste paper/cardboard and waste paper sludge) for cement-based composites [ 6 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%